2011
DOI: 10.1002/hec.1812
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐minimisation Analysis Versus Cost‐effectiveness Analysis, Revisited

Abstract: We aim to establish whether it is ever appropriate to conduct cost-minimisation analysis (CMA) rather than cost-effectiveness analysis.We perform a literature review to examine how the use of CMA has changed since Briggs & O'Brien announced its death in 2001. Examples of simulated and trial data are presented: firstly to illustrate the advantages and disadvantages of CMA in the context of non-inferiority trials and those finding no significant difference in efficacy and secondly to assess whether CMA gives bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 28 publications
1
65
0
Order By: Relevance
“…However, within the current paradigm, it is considered best practice that cost-effectiveness analysis should be conducted, because of the importance of estimating costs and effects jointly. 34 This study found that amoxicillin is associated with a cost-effectiveness ratio of €8216 (£6540) per QALY gained, indicating that the intervention is cost effective if the cost of resistance is ignored. The threshold at which the cost of resistances makes a difference to this decision is, however, low -between around €6 (£5) and €11 (£9) for the current NICE thresholds.…”
Section: Discussion Summarymentioning
confidence: 83%
“…However, within the current paradigm, it is considered best practice that cost-effectiveness analysis should be conducted, because of the importance of estimating costs and effects jointly. 34 This study found that amoxicillin is associated with a cost-effectiveness ratio of €8216 (£6540) per QALY gained, indicating that the intervention is cost effective if the cost of resistance is ignored. The threshold at which the cost of resistances makes a difference to this decision is, however, low -between around €6 (£5) and €11 (£9) for the current NICE thresholds.…”
Section: Discussion Summarymentioning
confidence: 83%
“…Even given that the EQ-5D changes were below those levels that are minimally important and were not significant, and the QALY gains were minimal (for acupressure vs standard care), one cannot evaluate the cost-effectiveness without considering costs. 82,83 Mean costs resulting from NHS resource use were consistently higher for the standard care only group than for the acupressure group; this finding was relatively robust to sensitivity analyses. However, because very little resource use was recorded in the study and the results may have been unduly influenced by outliers with high costs, this finding is relatively uncertain and must be treated with caution.…”
Section: Health-care Utilisation Datamentioning
confidence: 83%
“…14 A full methodological description of the study according to the MEEP reference case can be found in the appendix. Our approach also reflects the economic school of thought that, even when trial results find no significant evidence of an effect, a full cost-effectiveness analysis should be done, presenting all uncertainty in both costs and effects 15 …”
Section: See Online For Appendixmentioning
confidence: 99%